Hospital Performance Indicators and Their Associated Factors in Acute Child Poisoning at a Single Poison Center, Central Saudi Arabia. Issue 52 (December 2015) - Alanazi, Menyfah Q.; Al-Jeriasy, Majed I.; Al-Assiri, Mohammed H.; Afesh, Lara Y.; Alhammad, Fahad; Salam, Mahmoud
Abstract : Abstract: Admission rate and length of stay (LOS) are two hospital performance indicators that affect the quality of care, patients' satisfaction, bed turnover, and health cost expenditures. The aim of the study was to identify factors associated with higher admission rates and extended average LOS among acutely poisoned children at a single poison center, central Saudi Arabia. This is a cross-sectional, poison and medical chart review between 2009 and 2011. Exposures were child characteristics, that is, gender, age, body mass index (BMI), health history, and Canadian 5-level triage scale. Poison incident characteristics were, that is, type, exposure route, amount, form, home remedy, and arrival time to center. Admission status and LOS were obtained from records. Chronic poisoning, plant allergies, and venomous bites were excluded. Bivariate and regression analyses were applied. Significance at P < 0.05. Of the 315 eligible cases, (72%) were toddlers with equal gender distribution, (58%) had normal BMI, and (77%) were previously healthy. Poison substances were pharmaceutical drugs (63%) versus chemical products (37%). Main exposure route was oral (98%). Home remedy was observed in (21.9%), which were fluids, solutes, and/or gag-induced vomiting. Almost (52%) arrived to center >1 h. Triage levels: non-urgent cases (58%), less urgent (11%), urgent (18%), emergency (12%), resuscitative (1%). Admission rate was (20.6%) whereas av. LOS was 13 ± 22 h. After adjusting and controlling for confounders, older children (adj.OR = 1.19) and more critical triage levels (adj.OR = 1.35) were significantly associated with higher admission rates compared to younger children and less critical triage levels (adj. P = 0.006) and (adj. P = 0.042) respectively. Home remedy prior arrival was significantly associated with higher av. LOS (Beta = 9.48, t = 2.99), compared to those who directly visited the center, adj. P = 0.003. Hospital administrators are cautioned that acutely poisoned children who received home remedies prior arrival are more likely to endure an extended LOS. This non-conventional practice is not recommended.